Integration and expression of osmotin gene in Hevea brasiliensis, via Agrobacterium mediated transformation - Rekha, K.; Jayasree, R.; Sushamakumari, S.; Sobha, S.; Supriya, R.; Nazeem, P.A. (Journal of Plantation Crops, 2013)
-